Auditory Learning Style Dependence in the Digital Era: Its Influence on Students' Writing Skills - Nurazizah, Kurnia (Passikola: Jurnal Pendidikan Dasar & Madrasah Ibtidaiyah, 2025)
This study aims to analyze the influence of auditory learning styles on the writing ability of elementary school students in the digital era. This study uses a quantitative descriptive method with a survey approach. To collect data, a VAK questionnaire, a writing test, and classroom observation were used. The results show that 56% of students have an auditory dominant learning style. The average writing score of auditory students is 65.2, which belongs to the medium category, while non-auditory students achieve an average of 78.6, which belongs to the good category. Students who dominate the auditory learning style have difficulty in composing ideas, building paragraphs, and completing writing efficiently. This has an impact on how effective learning takes place and creates inequities in classroom interactions. This research emphasizes the importance of implementing multimodal learning strategies that can adjust various learning styles to improve students' writing skills.